Improving energy efficiency in residential buildings Kazakhstan. (Eurasian Journal of Ecology, 2016)
Energy efficiency is an indicator of scientific, technical and economic potential of a society that allows to assess the level of development. Economy of the Republic of Kazakhstan is characterized by high consumption of fuel and energy resources.More than 70% of the total takes the heating of buildings. In the developed countries of the European Union on home heating accounts for only 50% of all energy used. Energy efficient buildings constructed on European standards reduce energy consumption by 50-70% compared with conventional buildings. So, experts estimated that on heating one square meter in Kazakhstan consumes four times more energy than in other cold countries of Europe and in the United States- a country with a high thrustmaterial production, services and life. Electricity consumption per unit of GDP in Kazakhstan comparable to USA is higher 2.5 times, Germany and Japan 3.6 times.
Keywords: energy saving; energy; energy-efficiency; energy-efficient buildings; alternative technologies; the housing sector